NOMINALISASI BAHASA BALI (BB) - I Wayan Saryana (Universitas Warmadewa, 2017)
[Title: Nominalization in Balinese Language] The study deal with the process of nominal formation (nominalization) and Nominal structure of Balinese language. The data being analyzed is obtained from the researcher’s intuition that is the gained from language potency of the researcher as a native Balinese speaker. In addition, the data was also gained from Balinese texts such as novels, short stories, and folk tales. As a reference in analyzing the data it is applied X-bar theory developed by N, Chomsky and his adherers from the beginning of 1970-s. The most important essence of this theory is that every phrase structure has head. In other words, that every phrase structure is endocentric in nature. At the initial phrase, this theory was developed to describe phrasal category, then it was applied for clausal level. Recently, this theory is applied to analyze word level (Xo). Nouns in Balinese can be base and derived nouns. Derived nouns can be formed through some process: affixation, compounding, reduplication, and derivation of clauses. Nouns in Balinese can place syntactical functions such as subject, predicate, object, complement, and adverb.